Execution rates in Scottish witchcraft trials. - Willumsen, Liv Helene; Vassdal, Terje (Cogent Arts & Humanities, 2025)
This article estimates the total executions in Scottish witchcraft trials by using stratified sampling methods and random samples. The Scottish witchcraft trials took place in the period 1560–1727, and court records from these trials are preserved. However, the completeness of the source material varies. Information about these trials is registered in a data base: The Survey of Scottish Witchcraft. Out of the historical sources preserved, of a total of 3210 named cases, only 307 cases documenting verdict and sentence have survived. We assume that the surviving information on verdict and sentence has not been deliberately disposed of. Therefore, it is appropriate to use the method of statistical random sampling to analyse these documents. This article uses a methodology previously applied widely within social sciences, to include history, resulting in a novel interdisciplinary study. Our findings are that when we stratify the sample of preserved documents for verdict and sentence in three different ways, we get higher execution rates than previous historical studies. We argue that our results are more accurate than previous studies, and that our application of applied statistics on the historical source material manage to bring to the fore new and reliable results.